Negative Interest Rate Policy (NIRP) : Implications for Monetary Transmission and Bank Profitability in the Euro Area - Jobst, Andreas; Lin, Huidan (Washington, D.C. : International Monetary Fund, 2016)
More than two years ago the European Central Bank (ECB) adopted a negative interest rate policy (NIRP) to achieve its price stability objective. Negative interest rates have so far supported easier financial conditions and contributed to a modest expansion in credit, demonstrating that the zero lower bound is less binding than previously thought. However, interest rate cuts also weigh on bank profitability. Substantial rate cuts may at some point outweigh the benefits from higher asset values and stronger aggregate demand. Further monetary accommodation may need to rely more on credit easing and an expansion of the ECB's balance sheet rather than substantial additional reductions in the policy rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet